Neuroendocrine pathogenesis of perimenopausal depression - Han, Yuping; Gu, Simeng; Li, Yumeng; Qian, Xin; Wang, Fushun; Huang, Jason H. (Frontiers in Psychiatry, 2023)
With the development of social economics and the increase of working pressure, more and more women are suffering from long-term serious stress and showing symptoms of perimenopausal depression (PMD). The incidence rate of PMD is increasing, and the physical and mental health are seriously affected. However, due to the lack of accurate knowledge of pathophysiology, its diagnosis and treatment cannot be accurately executed. By consulting the relevant literature in recent years, this paper elaborates the neuroendocrine mechanism of perimenopausal depression from the aspects of epigenetic changes, monoamine neurotransmitter and receptor hypothesis, glial cell-induced neuroinflammation, estrogen receptor, interaction between HPA axis and HPG axis, and micro-organism-brain gut axis. The purpose is to probe into new ways of treatment of PMD by providing new knowledge about the neuroendocrine mechanism and treatment of PMD.